E-074 Pipeline Strategies. (14th July 2013) - Urdaneta, A; Darflinger, R; Chao, K; Feng, L
Abstract : Background: Pipeline Embolisation Device (PED) is a flow diversion stent for the treatment of large wide neck aneurysms that are not well treated with coiling methods including stent assisting coiling. The PED material and design are relatively unique including its deployment. Objective: Evaluation of the PED procedures including issues during deployment and strategies to outcome problems. Methods: Retrospective multicentreed case series of 30 PED procedures for treatment of aneurysms. The cases were evaluated for issues that arose during PED deployment. The different strategies for managing problems was assessed for their effectiveness. Results: There were eight major issues with PED deployment. 1. Detachment from capture coil, 2. PED apposition to the vessel wall, 3. Torqueing or twisting of the PED, 4. Accurate placement of the PED, 5. Herniation of PED into aneurysm, 6. Advancing the microcatheter and removing the delivery system, 7. Accessing the distal outflow artery, and 8. Post procedure stroke within 3 days. Successful treatment strategies for each of the major issues demonstrated reasonable success. Conclusion: PED is a 1st generation flow diversion stent with a variety of issues related to its deployment. However, familiarity with PED deployment strategies can result in a more successful deployment. Disclosures: A. Urdaneta: None. R. Darflinger: None. K. Chao: None. L. Feng: None.